As contribuições ao PIS e a COFINS e a aplicabilidade do princípio constitucional da não cumulatividade - Santos, José Aparecido dos [UNESP] (2014)
The contribution of non-cumulative PIS and COFINS was always complain taxpayers, citizens, businessmen, mainly from the clear understanding that all have the harmful effects and majoradores the tax burden arising from its cascading effect. Taxes like these are considered economically perverse, because they are actually manifestations of an impact on ability to pay previously reserved for other tax implications of institutionalizing the undesirable bis in idem. But not in its theoretical conception of double effect on one same economic data, but representing a sequence of cascading effects that overlap. Given this scenario, the claims by the prevalence and applicability of non-cumulative PIS and COFINS are increasing. To know the possibility of the application of this systematic referred to Social Contributions sought to improve them within the Brazilian tax system, which proved, according to the theory pentapartite a tax subspecies, species Special Contributions, which belongs to gender tribute side of the taxes, fees, contributions and Compulsory Loans Improvements. Once framed within the concept of tax, legal and constitutional rules must be observed. And it is in this sense that it draws a parallel between the materiality of the PIS and COFINS, with other taxes such as IPI and ICMS in order to observe the conditions of a noncumulative taxation, because until then the PIS and COFINS were being taxed cumulatively, damaging the national economy, since the incidence cascading propitiated an increased tax burden. And, in a context where the taxman stands out increasingly by their tax collection office, the search for solutions that remediam high tax burden increases every day in Brazil. In this vein, in order to eliminate the cumulative nature of these contributions, which, in theory, increase the cost and would burden the chain of production, Laws were published paragraphs. 10.637 / 02 and 10.833 / 03, changing the dynamics of...